Psychological Profiles of Child Sex Offenders: Insights from Indonesia and International Perspectives - Nuqul, Fathul Lubabin; Mufida, Aulia Zahwa; Muhammad, Fathimah Zahra; Anam, Hizbi Maulana Alfath; Nela, Nisa Naja (International Conference on Law, Technology, Spirituality and Society (ICOLESS), 2025)
This article outlines the significance of psychological profiling in the management of sexual crime cases against children, specifically in the Indonesian situation. Psychological profiling as a method of crime resolution and prevention examines the personality of the crime scene, the victim's profile, and the offender's behavior in order to speculate about the offender's psychological traits, motives, and modus operandi. Suspect profiling needs to be adapted to the local legal framework and culture. Prevention and intervention programs need to be attuned to the local cultural context and respond to underlying socio-economic factors for sexual violence prevalence. Community-based initiatives can promote awareness and reporting of suspected incidents of violence. Interagency collaboration is needed to stage a concerted and multistranded response to child sexual offending.